DISCOURSE OF HIZBUT TAHRIR INDONESIA'S RADICALISM: A CRITICAL DISCOURSE ANALYSIS ON TEMPO.CO MEDIA - Sarmadan Sarmadan; Aceng Rahmat; Siti Gomo Attas (Getsempena English Education Journal, 2022)
Hizbut Tahrir Indonesia (HTI) radicalism discourse invites polemics and pros and cons that have not ended. The various perspectives on the existence until the dissolution of the mass organization need to be understood in depth, objectively, and comprehensively. This research was conducted with the aim of comprehensively dissecting the discourse of HTI radicalism which wants to substitute the Pancasila ideology by carrying the caliphate ideology. This research is a literature study using a qualitative approach. The knife of analysis is the critical discourse analysis of Norman Fairclough's model which consists of three dimensions of analysis, namely text analysis, discourse practice, and sociocultural practice. The data in this study are texts in the form of vocabulary, sentences, or discourses whose corpus is from a news story entitled "The Rise of HTI Rejection, Said Aqil: The Governor Must Be Able To Build Citizens" published by Tempo.co on Friday, May 5, 2017. The results show that in In terms of text analysis, especially in terms of diction and textual structure, Tempo.co represents the rejection of the caliphate ideology promoted by HTI which is reflected in the use of diction which has a positive meaning. The textual structure uses a strategy of accommodating sources as a news construction database. This can be seen in the construction of news where the four components, namely 1) news title, 2) selection of sources, 3) positioning of source quotes, and 4) the quantity of sources' statements lead to the collectivity of the meaning of rejection of the ideology of the HTI caliphate. Likewise, in the aspect of discourse practice, it is illustrated that the construction of Tempo.co news is in line with the public perspective which rejects HTI's radical ideology, as well as socio-cultural practices that strengthen or strengthen public knowledge and awareness that the disbandment of HTI must be carried out immediately because it can threaten the existence of Pancasila, UUD 1945, dan NKRI.